Role of Radioprotectors in the Inhibition of DNA Damage and Modulation of DNA Repair After Exposure to Gamma-Radiation - Maurya, Dharmendra Kumar; Devasagayam, Thomas Paul Asir (IntechOpen, 2011)
None